Leaking laffs between Pampers and Depends ; He's gonna toot and I'm gonna scoot ; Living somewhere between estrogen and death /: He's gonna toot and I'm gonna scoot ; Living somewhere between estrogen and death. (2002) - Johnson, Barbara (Barbara E.)
No abstract available